Climate Change, Securitisation of Nature, and Resilient Urbanism. (April 2014) - Davoudi, Simin
Climate change is a powerful reminder of the interdependencies of the human–nature relationship and the fallacy of the modernist assumption about our ability to tame nature for our exploitation with little or no consequences. However, it is argued that such reflexivity is being subverted by the dominant discourses of climate change which portray: nature as risk, our relation to it in terms of security, and the quest for urban resilience as emergency planning. By construing nature as a threat to rather than an asset for cities, they signify a departure from sustainability discourses. They represent a hark back to a premodern conception of human–nature relations that was centred on what nature does to us rather than what we do to nature . Seeing nature as risk ushers in deep concerns with security. The 'risk society' becomes entwined with the security society. This paper examines the political implications of this discursive shift and argues that, as securitisation becomes the hegemonic discourse of our time, the postpolitics of hope, which underpinned sustainability, is giving way to the postpolitics of fear which underlies climate change.